The Influence of Occupational Health and Safety and Employee Competence on Risk Mitigation Affecting the Operational Performance of the Port at PT Pelindo IV Pare Pare Port - Ardiansyah, Ardiansyah; Sumali , Bambang (Dinasti Publisher, 2024)
This study aims to analyze the impact of occupational health and safety and employee competence on risk mitigation that affects the operational performance of the port at PT Pelindo IV Pare Pare Port. The issues addressed concern how these two factors can influence risk mitigation and operational performance. The study population consisted of 168 employees, with a sample taken using purposive sampling and simple random sampling methods, resulting in 118 respondents. The research employs a quantitative descriptive approach with a cross-sectional design. Data were collected through questionnaires and analyzed using SmartPLS. The findings indicate that occupational health and safety and employee competence have a positive and significant impact on risk mitigation, and both directly contribute to improving the port's operational performance. Furthermore, risk mitigation is shown to function as a mediator in this relationship. The conclusion emphasizes the importance of enhancing safety measures and employee competence to promote better operational performance at the port.